The reporting of pulmonary nodule results by letter in a lung cancer screening setting. (June 2022) - Dickson, Jennifer L; Bhamani, Amyn; Quaife, Samantha L; Horst, Carolyn; Tisi, Sophie; Hall, Helen; Verghese, Priyam; Creamer, Andrew; Prendecki, Ruth; McCabe, John; Gyertson, Kylie; Bowyer, Vicky; et al.
Highlights: High participant satisfaction with the communication of pulmonary nodule results by letter. Most participants would choose to receive pulmonary nodule results by letter. The majority felt that their results letter contained the right amount of information. A significant minority of participants had discussed the results with their GP. Abstract: Objectives: Pulmonary nodules are commonly found in Lung Cancer Screening (LCS), with results typically communicated by face-to-face or telephone consultation. Providing LCS on a population basis requires resource efficient and scalabe communication methods. Written communication provides one such method. Here, we assess participant satisfaction with this approach in a LCS setting and investigate characteristics associated with dissatisfaction. Materials and methods: The SUMMIT Study is a prospective observational cohort study which aims to assess the implementation of Low-Dose Computed Tomography (LDCT) scanning for LCS in a high-risk population and validate a multi-cancer early detection blood test (NCT03934866). Participants with indeterminate pulmonary nodules requiring a three-month interval LDCT were informed of their result by postal letter and given a face-to-face appointment with a study practitioner at their interval LDCT appointment. At this appointment, having previously received their results letter, participants were verbally asked questions to assess their satisfaction with, and preferences for, methods of results communication. Results: 1, 900 participants were included in the analysis. 82.8% (n = 1573) were satisfied with receiving their results by letter, with 2.9% (n = 55) reporting dissatisfaction. 86.3% (n = 1640) stated it was their preferred communication method and 77.3% (n = 1469) reported that their letter contained the right amount of information. Participants from less deprived socioeconomic quintiles were more likely to report that the letter contained insufficient information and individuals aged ≥ 70 years were less likely to do so. Although 13.7% (n = 261) participants had discussed their results with their General Practitioner (GP) prior to the study visit, 83.9% (n = 219) of these participants were satisfied with receiving results by letter, with the same proportion preferring this communication method. Conclusion: We report high participant satisfaction with the reporting of pulmonary nodule results by letter in a LCS setting. We believe this provides a feasible route forward for large-scale screening programmes.